Current progress in non-viral vectors for cancer gene therapy - Ichwan, Solachuddin J. A. (2017)
Cancers are generally treated by radiotherapy, chemotherapy and radical surgery alone, or combination of these treatments. Selection of the treatment, depending on the type, location, size and stage of tumor. However, such conventional therapies are non-selective and can cause damage to normal tissue. Cancer gene therapy is a treatment method that has been developed to selectively destroy cancer cells by introducing "therapeutic gene" into targeted cancer cells while sparing normal tissues. The success of gene therapy is dependent on the choice of the gene delivery system, which is either viral or non-viral vector. Currently, recombinant viral vectors widely used because of their gene transduction and high loading capacity. However, administration of viral vectors is hampered by a number of drawbacks such as host's immune responses, tedious, time consuming, expensive and environmental risk concern in preparation. Although non-viral vectors are less efficient than viral ones, they have the advantages of safety, simplicity of preparation and high gene encapsulation capability. This brief review highlights the recent progress and challenges in the development of non-viral vectors for cancer gene therapy and opportunities for their potential use in clinical trials.